Peran Para Bhikkhu dalam Penguatan Mental Umat Buddha di Lombok Utara Pasca Gempa 2018 - Lian Febrianti; Sentot; Aryanto Firnadi (STAB Kertarajasa, 2025)
This study aims to determine the mental condition of Buddhists in North Lombok after the 2018 earthquake and analyze the role of monks in strengthening the mental health of the community. This study uses a qualitative approach with a descriptive type. Data collection techniques include interviews, observations, and documentation. Data analysis is conducted through data condensation, data presentation, and conclusion drawing/verification. Data sources consist of primary data from interviews with monks, priests, and affected communities, as well as secondary data from books, journals, and relevant online sources. The results of the study show that Buddhists in North Lombok experienced psychological disorders such as stress, trauma, anxiety, and post-disaster sleep disorders. In this situation, the monks were actively present to provide spiritual support through Dhamma lectures, meditation practices, individual counseling, and social-religious activities. Their role is not only to entertain or comfort, but also to facilitate recovery and strengthen the inner strength and psychological resilience of the community. In conclusion, the role of monks is very important in helping the community cope with the psychological impact of disasters. They are not only conveyors of religious teachings, but also spiritual companions and facilitators in building mental resilience through a holistic spiritual, social, and psychological approach. The presence of monks is a key factor in the recovery process, leading the community towards a more stable, peaceful, and hopeful life.